Controlling Self‐Sorting versus Co‐assembly in Supramolecular Gels. Issue 4 (14th April 2022) - Panja, Santanu; Dietrich, Bart; Smith, Andrew J.; Seddon, Annela; Adams, Dave J.
Abstract: Supramolecular gels formed by the combination of different organic molecules are of significant interest in the search of new functional materials. When two different molecules are mixed to form gels, the self‐assembled fibres can be a result of self‐sorting or co‐assembly. A key challenge is to control the network type. Here, we demonstrate that control over the network type can be achieved either by varying the hydrophobicity of a component or by employing a pH‐switch method. Abstract : Self‐sorting or co‐assembly ? The control over the network type in multicomponent gels can be achieved either by varying the hydrophobicity of a component or by changing the preparative pathway.